Shorter and Improved Access to the Key Tetracyclic Core of Sarpagine-Macroline-Ajmaline Indole Alkaloids: the Total Synthesis of Alkaloids Macrocarpines A-g, Talcarpine, N(4)-methyl-n(4),21-secotalpinine, Deoxyperaksine, Dihydroperaksine, Talpinine, O-acetyltalpinine, and N(4)-methyltalpinine - (:unkn) unknown (My University, 2018)
Extension of the asymmetric Pictet-Spengler (P-S) reaction to bulkier Nb-alkylated tryptophan derivatives resulted in a shorter and improved stereospecific access to the key bicyclo[3.3.1]nonane framework of bioactive C-19 methyl substituted sarpagine/macro-line/ajmaline indole alkaloids with excellent diastereoselectivity via internal asymmetric induction. The asymmetric Pictet-Spengler/Dieckmann protocol with bulky Nb-alkyl substituted systems enabled a more direct and two-step shorter route to this key architecture. Complete stereocontrol of the C-19 methyl function in either the α- or β-configuration was achieved which would enable one to gain rapid access to the crucial intermediates for the total synthesis of any member of this group of seventy alkaloids. The asymmetric Pictet-Spengler (P-S) reaction of chiral Nb-ethynyl substituted tryptophan methyl ester derivatives (from both D- and L-tryptophan) with a simple aliphatic aldehyde, exhibited unprecedented stereoselectivity toward either of the diastereomeric products. A simple variation of conditions altered the outcome of the cyclization from either 100% trans-selective to 100% cis-selective originating entirely from internal asymmetric induction under mild conditions. This resulted in the highly efficient access to both 1,3-cis-(1,2,3-trisubstituted tetrahydro-β-carbolines, THβCs) and 1,3-trans-(1,2,3-trisubstituted THβCs). By exploiting this very useful ambidextrous-diastereoselectivity, one can set the crucial C-3 and C-5 stereocenters of the C-19 methyl substituted sarpagine-macroline-ajmaline alkaloids beginning either with the DNA-encoded and cheaper L-(-)-tryptophan, as well as optionally from commercially available D-(+)-tryptophan. The unnatural enantiomers of bioactive natural alkaloids are potential drug candidates. The unnatural enantiomer of alkaloids may have similar drug-like properties or even better than the natural counterpart depending on the rate of metabolism. The ambidextrous Pictet-Spengler reaction has enabled one to access the key intermediates with the bicyclo[3.3.1] framework starting from either the natural L-tryptophan or the commercially available D-tryptophan. Logically, the ambidextrous nature of this P-S process would allow one ready access to the unnatural enantiomers of the alkaloids from this subgroup. As the proof of concept, which is important to illustrate the full potential of the ambidextrous P-S reaction, both D-tryptophan and L-tryptophan were employed to synthesize the key intermediates toward the natural enantiomers of alkaloids. Now the enantiomeric series of the same key intermediates could also be synthesized from both D- and L-tryptophan in high yield and optical purity via this P-S/Dieckmann protocol. One can make either the natural or the unnatural alkaloids from either starting amino acid ester, stereo and enantiospecifically at will. After gaining access to the bicyclo[3.3.1] framework via the ambidextrous Pictet-Spengler reaction, the focus turned to the completion of the total synthesis of a number of C-19 methyl substituted sarpagine/macroline/ajmaline indole alkaloids. As a step towards that, alkaloids with Na-H, Nb-CH3 substitution patterns were both of interest via the same route. An enolate driven copper-mediated cross-coupling process enabled a cheaper and greener access to the key pentacyclic intermediates required for the enantiospecific total synthesis of a number of C-19 methyl substituted sarpagine/macroline indole alkaloids. Replacement of palladium (60-68% yields) with copper iodide (82-89% yields) resulted in a much cleaner process in high yield. The formation of an unusual seven-membered cross-coupling product was completely inhibited by using TEMPO as a radical scavenger. Further functionalization led to the first enantiospecific total synthesis of macrocarpines D and E. After the successful completion of the total synthesis of several C(19)-methyl Na-H, Nb-CH3 substituted alkaloids, focus turned toward the total synthesis of a number of alkaloids bearing the Na-CH3, Nb-CH3 substitution pattern. In addition, a pair of sarpagine alkaloids, termed dihydroperaksine and deoxyperaksine bore the C-19 (S)-methyl substitution; this was opposite to the chirality in many of the alkaloids of this group. Access to these alkaloids in high yields illustrated the versatility of the strategy developed here to access alkaloids with either C-19 (S)- or (R)-methyl substituents. This effort resulted in the successful total synthesis of several bioactive alkaloids, as well as correction of the literature values for macrocarpine A and N4-methyl-N4,21-secotalpinine. A late stage Nb-demethylation of macrocarpines A and C afforded the Nb-H bearing alkaloids macrocarpines F and G, respectively. A similar transformation enabled access to the bioactive alkaloid talpinine from both talcarpine and N4-methyl-N4,21-secotalpinine. The other bioactive alkaloid O-acetyltalpinine was also prepared from synthetic talpinine in high yield. Finally, the unusual quaternary Nb-nitrogen function containing alkaloid N4-methyltalpinine that exhibited potent NFκB inhibitory activity was completed via facile transformations in excellent yield.
Keywords: Asymmetric Pictet-Spengler Reaction; Bioactive Indole Alkaloids; Sarpagine-Macroline-Ajmaline; Total Synthesis; Unnatural Enantiomers